Plasma and Magnetic Field Turbulence in the Earth’s Magnetosheath at Ion Scales - Rakhmanova, Liudmila; Riazantseva, Maria; Zastenker, Georgy (Frontiers in Astronomy and Space Sciences, 2021)
Crossing the Earth's bow shock is known to affect crucially the solar wind plasma including changes in turbulent cascade. Present review summarizes results of more than 15 years of experimental exploration of the magnetosheath turbulence. Great contribution to understanding of turbulence development inside the magnetosheath was made by means of recent multispacecraft missions. We introduce the main results provided by them together with first observations of the turbulent cascade based on direct plasma measurements by Spektr-R spacecraft in the magnetosheath. Recent results on solar wind effects on the turbulence in the magnetosheath are also discussed.